Opinia wyborców o integracji Polski z Unią Europejską a preferencje i aktywność wyborcza - Liszkowska, Julia (Political Preferences, 2011)
The present article aims to describe the relationship between political preferences of voters in different types of Polish elections (local, parliamentary, presidential) or of citizens inactive in the elections and their opinion on the integration of Poland with the EU as positive or negative. The results are based on a poll carried out at the end of 2010. The voters were asked about the political parties and groups they support in different elections (or specific persons